Collapse: America Will Fall - Richard Stephenson (b. 1975) (Stevenson & Powers Publishing House, 2012)
Dystopia in which the U.S. faces internal and external threats and a Second Great Depression. In a sequel, Resistance: America Has Fallen. Ed. Susan Hughes. Np: Richard Stephenson, 2013, the U.S. has been torn apart and the main protagonists in Collapse are trying to save it. A third volume was announced but has not appeared. A related story with characters from Collapse, “Spider: A Short Story.” Ed. Susan Hughes (2012) has been published on Kindle.
Keywords: Male author; US author